A trick of the tail: the role of social networks in shaping distributional properties of experience-good markets. (8th August 2018) - Babutsidze, Zakaria; Valente, Marco
Abstract: The diffusion of social media has radically changed the number of peers with whom consumers interact with when making a decision. While consumption decisions depend on many factors, such as prices, qualities, distribution channels, and marketing, in this article, we study the effects of a single aspect: the role of the number of social connections in shaping consumers' decisions. We present an agent-based simulation model where virtual consumers respond solely to information provided by peers from their social network. We obtain that increasing the number of connections consumers rely upon to gather information changes radically the distributional properties of markets where consumers cannot obtain direct information about the available options, such as experience goods. In particular, we show that increasing the number of connections among consumers increases the concentration of the top- and low-end market share options, sharply decreasing the number of "mid-sized" options. This effect is in line with evidence from markets for movies and music, which rely heavily on information gathered through peers.